Design of a system of continuous ecological education as a base of transition to a model of sustainable development - V. N. Ekzaryan; A. V. Mazaev (Известия высших учебных заведений: Геология и разведка, 2017)
The problems and approaches to the designing of a system of a continuous ecological education are discussed. A model of an environmental education at different levels: preschool, school, higher education and professional retraining is proposed. The aims, tasks, approaches to the organization of higher environmental education are shown on the example of MGRI-RSGPU. The principles of an environmental education with sustainable development of future generations and the whole biosphere are proposed.